Evaluation of Pharmaceutical Wastewater Treatment Effluent at PT. X, Surabaya City - Sari, Mega Mutiara; Suryawan, I Wayan Koko (Journal of Sustainable Infrastructure, 2025)
PT. X is a pharmaceutical company that produces wastewater with the potential to harm the environment. Although the company already has a wastewater treatment system in place, this study evaluates its performance through direct field surveys and qualitative analysis based on ideal treatment standards. The treatment system at PT. X uses a series of five stabilization tanks operated in a continuous flow. However, BOD and COD test results from November 2019 to March 2020 show that the treated effluent does not meet the required pharmaceutical wastewater quality standards. This indicates the need to redesign the existing treatment system. One solution is to improve the biological treatment process, as the current BOD/COD ratio of around 0.5 suggests poor biodegradability. In addition, introducing an electrocoagulation process could enhance performance, with COD removal efficiency reaching up to 55.4%.